Ritual: An introduction - Pickstock, Catherine (International journal of philosophy and theology, 2018)
This introduction gives an overview of the present volume and suggests that it is possible to speak of an emerging ritual' or liturgical' turn within theology. This turn seems able to mediate between four different dualities, and to open out new perspectives that are at once traditional and innovative.